Hepcidin is an antibacterial, stress-inducible peptide of the biliary system - Strnad, Pavel; Schwarz, Peggy; Rasenack, Maria C. D.; Kucukoglu, Ozlem; Habib, Rayan I.; Heuberger, Dominik; Ehehalt, Robert; Müller, Michael W.; Stiehl, Adolf; Adler, Guido; Kulaksiz, Hasan (PLOS ONE, 2011)
Background/Aims Hepcidin (gene name HAMP), an IL-6-inducible acute phase peptide with antimicrobial properties, is the key negative regulator of iron metabolism. Liver is the primary source of HAMP synthesis, but it is also produced by other tissues such as kidney or heart and is found in body fluids such as urine or cerebrospinal fluid. While the role of hepcidin in biliary system is unknown, a recent study demonstrated that conditional gp130-knockout mice display diminished hepcidin levels and increased rate of biliary infections. Methods Expression and localization of HAMP in biliary system was analyzed by real time RT-PCR, in-situ hybridization, immunostaining and -blotting, while prohepcidin levels in human bile were determined by ELISA. Results Hepcidin was detected in mouse/human gallbladder and bile duct epithelia. Biliary HAMP is stress-inducible, in that it is increased in biliary cell lines upon IL-6 stimulation and in gallbladder mucosa of patients with acute cholecystitis. Hepcidin is also present in the bile and elevated prohepcidin levels were observed in bile of primary sclerosing cholangitis (PSC) patients with concurrent bacterial cholangitis compared to PSC subjects without bacterial infection (median values 22.3 vs. 8.9; p = 0.03). In PSC-cholangitis subjects, bile prohepcidin levels positively correlated with C-reactive protein and bilirubin levels (r = 0.48 and r = 0.71, respectively). In vitro, hepcidin enhanced the antimicrobial capacity of human bile (p<0.05). Conclusion Hepcidin is a stress-inducible peptide of the biliary epithelia and a potential marker of biliary stress. In the bile, hepcidin may serve local functions such as protection from bacterial infections.